Integration for development — Hopes and problems - Ekkehard Bechler (Intereconomics, 1976)
The following article deals with the conditions under which regional associations in the Third World can improve the economic situation of the developing countries and the question how suitable they are for this purpose.
Keywords: 330; Regional Associations